Maize resistance to insect herbivory is enhanced by silencing expression of genes for jasmonate‐isoleucine degradation using sugarcane mosaic virus. (9th June 2022) - Chung, Seung Ho; Zhang, Shudi; Song, Hojun; Whitham, Steven A.; Jander, Georg
Abstract: Previously, sugarcane mosaic virus (SCMV) was developed as a vector for transient expression of heterologous genes in Zea mays (maize). Here, we show that SCMV can also be applied for virus‐induced gene silencing (VIGS) of endogenous maize genes. Comparison of sense and antisense VIGS constructs targeting maize phytoene desaturase (PDS) showed that antisense constructs resulted in a greater reduction in gene expression. In a time course of gene expression after infection with VIGS constructs targeting PDS, lesion mimic 22 ( Les22 ), and Iodent japonica 1 ( Ij1 ), efficient expression silencing was observed 2, 3, and 4 weeks after infection with SCMV. However, at Week 5, expression of Les22 and Ij1 was no longer significantly reduced compared with control plants. The defense signaling molecule jasmonate‐isoleucine (JA‐Ile) can be inactivated by 12C‐hydroxylation and hydrolysis, and knockout of these genes leads to herbivore resistance. JA‐Ile hydroxylases and hydrolases have been investigated in Arabidopsis, rice, and Nicotiana attenuata . To determine whether the maize homologs of these genes function in plant defense, we silenced expression of ZmCYP94B1 (predicted JA‐Ile hydroxylase) and ZmJIH1 (predicted JA‐Ile hydrolase) by VIGS with SCMV, which resulted in elevated expression of two defense‐related genes, Maize Proteinase Inhibitor ( MPI ) and Ribosome Inactivating Protein 2 ( RIP2 ). Although ZmCYP94B1 and ZmJIH1 gene expression silencing increased resistance to Spodoptera frugiperda (fall armyworm), Schistocerca americana (American birdwing grasshopper), and Rhopalosiphum maidis (corn leaf aphid), there was no additive effect from silencing the expression of both genes. Further work will be required to determine the more precise functions of these enzymes in regulating maize defenses.